Investigating the molecular mechanisms underlying the differential virulence of Salmonella enterica serovars Typhimurium and Choleraesuis - Johnston-Menzies, Imogen Rena (The University of Edinburgh, 2021)
Salmonella enterica is a facultative intracellular pathogen which impacts human and animal health globally. Livestock animals, as a source of nutrition and environmental contamination, represent a significant reservoir for human non-typhoidal salmonellosis. For Salmonella enterica serovars, systemic dissemination to sites outwith the intestinal environment is a phenotypic marker of bacterial host-adaptation, a trait which influences infection outcome. Host-adapted Salmonella Choleraesuis, for example, disseminates to the bloodstream, liver, and spleen of infected pigs, causing little intestinal inflammation but greater mortality whilst host-generalist Salmonella Typhimurium causes self-limiting enteritis. S. enterica encodes two type III secretion systems (T3SSs) which have critical roles in bacterial pathogenesis – the T3SS-1 and T3SS-2. Both systems are molecular syringes that inject effector proteins into host cells. These effectors manipulate host-cell processes to aid either invasion (T3SS1) or intracellular survival (T3SS-2). As significant evidence suggests that type III secretion influences host adaptation, the first aim of this study was to characterise and compare the secretome of host-generalist S. Typhimurium and host-adapted serovar S. Choleraesuis under T3SS-1 inducing conditions. A label-free quantitative proteomics approach was used to characterise the secretome of two strains of well-defined virulence in livestock animals – S. Typhimurium ST4/74 and S. Choleraesuis SCSA50 – and identified key differences between the strains. This was the first comprehensive and quantitative comparison between the secretomes of two different nontyphoidal S. enterica serovars and demonstrated that ST4/74 secreted more T3SS-1 effectors than host-adapted SCSA50, a result which could not have been predicted from the genome sequences alone. In addition, the proteomic approach also identified several hypothetical proteins which were investigated for T3SS-dependent secretion. The subsequent aim of this study was to unravel regulatory differences between ST4/74 and SCSA50 at the transcriptional level using quantitative reverse transcription PCR (RT-qPCR). Initial comparative bioinformatic analysis revealed single nucleotide polymorphisms in important regions of the promoters of several factors which control T3SS-1 expression including major transcriptional regulators HilA and HilE. Consequent RT-qPCR investigation uncovered small but biologically relevant increases in transcriptional expression of T3SS-1 transcriptional activators by ST4/74 compared to SCSA50 which could explain the differences in effector protein secretion. The importance of the T3SS is, however, in the context of host cells. The last aim of this study was therefore to examine the interactions of ST4/74 and SCSA50 with porcine cell lines using assays to assess invasion, intracellular survival, net replication, and intracellular cytosolic populations. Whilst the strains were similarly invasive, their intracellular lifestyles differed – in the intestinal cell line IPEC-J2, ST4/74 replicated faster and had a larger cytosolic population than SCSA50, two bacterial intracellular strategies linked to activity of T3SS-1. Overall, this study revealed significant differences in the repertoire and amount of secreted proteins by host-generalist ST4/74 and host-adapted SCSA50. Although more mechanistic exploration is required, increased transcriptional expression of T3SS-1 transcriptional activators by ST4/74 potentially influences this. Paired with the differences in intracellular lifestyle, this investigation identified type III secretion as a major differentiating factor between S. Typhimurium and S. Choleraesuis and this data could inform on new strategies for crucial broad-spectrum vaccine design.